2011
DOI: 10.1093/jxb/err301
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin GRXS13 plays a key role in protection against photooxidative stress in Arabidopsis

Abstract: Glutaredoxins (GRXs) belong to the antioxidant and signalling network involved in the cellular response to oxidative stress in bacterial and eukaryotic cells. In spite of the high number of GRX genes in plant genomes, the biological functions and physiological roles of most of them remain unknown. Here the functional characterization of the Arabidopsis GRXS13 gene (At1g03850), that codes for two CC-type GRX isoforms, is reported. The transcript variant coding for the GRXS13.2 isoform is predominantly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 60 publications
2
83
0
4
Order By: Relevance
“…Despite the generation of two affinity-purified peptide antibodies targeting different regions of the AtGRXS3 protein, none of the corresponding glutaredoxin proteins could be detected by immunoblotting. This finding is consistent with the absence of protein abundance data in previous studies of class III glutaredoxins (Xing et al, 2005;Xing and Zachgo, 2008;La Camera et al, 2011;Laporte et al, 2012) and in large-scale nontargeted proteomics studies (Baerenfaller et al, 2008), likely reflecting the very low abundance of these proteins in vivo (Ströher and Millar, 2012).…”
Section: Functional Analyses Of Nitrate-regulated Glutaredoxinssupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the generation of two affinity-purified peptide antibodies targeting different regions of the AtGRXS3 protein, none of the corresponding glutaredoxin proteins could be detected by immunoblotting. This finding is consistent with the absence of protein abundance data in previous studies of class III glutaredoxins (Xing et al, 2005;Xing and Zachgo, 2008;La Camera et al, 2011;Laporte et al, 2012) and in large-scale nontargeted proteomics studies (Baerenfaller et al, 2008), likely reflecting the very low abundance of these proteins in vivo (Ströher and Millar, 2012).…”
Section: Functional Analyses Of Nitrate-regulated Glutaredoxinssupporting
confidence: 91%
“…The seven glutaredoxin genes identified as strongly and specifically induced by nitrate in our data are all class III. Only four of the 21 class III glutaredoxin genes in the Arabidopsis genome have been functionally characterized (Xing et al, 2005;Xing and Zachgo, 2008;La Camera et al, 2011;Laporte et al, 2012), and no functional information is available about any of the identified nitrate-induced glutaredoxins.…”
Section: Functional Analyses Of Nitrate-regulated Glutaredoxinsmentioning
confidence: 99%
“…Nine of the 30 glutaredoxin genes in the Arabidopsis genome were identified as being up-regulated by cytokinin. The functions of glutaredoxins in plants are only beginning to be elucidated (Rouhier et al, 2008), but include roles in the protection against photooxidative stress (Laporte et al, 2012), ironsulfur cluster assembly, flower development (Wang et al, 2009), and pathogen response (Wang et al, 2009). The cytokinin regulation of multiple glutaredoxin genes suggests a link to these processes.…”
Section: Differential Expression Analysis Of Rna-seq Datamentioning
confidence: 99%
“…Rather than create a new gene model 15 , AT5G05860 (UGT76C2) 16 , AT5G56970 (CKX3) 17 , AT2G17820 (AHK1) 18 21 , AT1G74890 (ARR15) 22 , AT1G59940 (ARR3) 23 , AT1G19050 (ARR7) 23 , AT3G48100 (ARR5) 23 , AT3G57040 (ARR9) 23 , AT5G62920 (ARR6) 23 , AT2G41310 (ARR8) 23 , AT2G28160 (bHLH029) 24 , AT2G22770 (NAI1) 25 , AT4G26150 (CGA1) 26,27 , AT1G10480 (ZFP5) 28,29,30 , AT1G16530 (ASL9) 31 , AT1G04240 (SHY2) 13 , AT1G72360 (ERF73) 32 , AT2G40970 (MYBC1) 33 , AT1G71030 (MYBL2) 34 , AT5G65210 (TGA1) 35 , AT2G21650 (MEE3), AT4G39070 (B-box zinc finger), AT5G50915 (bHLH), AT4G23750 (CRF2), AT2G40670 (ARR16), AT1G10470 (ARR4), AT4G25410 (bHLH), AT1G18400, AT1G04250 (BEE1), AT2G27840 (HDT4), AT1G67030 (ZFP6), AT1G68360 (C2H2), AT3G48920 (bHLH), AT5G05790 (Homeodomain), AT3G04070 (ANAC047), AT1G68880 (ZIP), AT5G15830 (ZIP3), AT1G31320 (LBD4), AT3G50700 (IDDT2) 1 Ralph et al (2007). 3 Laporte et al (2012). 4 Wang et al (2009).…”
Section: New Gene Models and Alternative Splicing In Genes Involved Imentioning
confidence: 99%
“…Several Arabidopsis (Arabidopsis thaliana) GRXs from class III participate in the tolerance to photooxidative stress (Laporte et al, 2012) and defense against pathogens (Ndamukong et al, 2007;La Camera et al, 2011). Others are required for proper reproductive development through interaction with basic Leu zipper-type TGA transcription factors (Xing and Zachgo, 2008;Murmu et al, 2010).…”
mentioning
confidence: 99%